Advances in advertising research (Vol. 2) breaking new ground in theory and practice - Okazaki, Shintaro (Springer eBooks., 2011)
Advances in Advertising Research series are published annually by the European Advertising Academy (EAA). This volume grew out of research papers presented at the 9th ICORIA (International Conference on Research in Advertising) which was held at Universidad Autónoma de Madrid, Spain, on June 24-26, 2010. The conference involved advertising, communication, and marketing scholars located all over the world, thereby setting an example of diversity and plurality in our ICORIA community. The goal of this book is breaking new ground in both theory and practice. Each chapter tries to shed light on challenging topics and offer insights that are of considerable value for advancing our knowledge.